Brand image of nursing perceived by rural society in the wake of Covid-19 in Indonesia - Noviani, Wulan; Alimuddin, Muh. Ihya; Suprabowo, Imam; Mei Chan, Chong; Jamaludin, Thandar Soe Sumaiyah (Universiti Putra Malaysia Press, 2025)
Stereotypes of nursing still exist in society. Furthermore, since the Covid-19 outbreak in Indonesia, the brand image of nursing has been limited in exploring for rural society. This study aims to explores the public’s perception of nursing brand image in the wake of Covid-19 in Indonesia, especially in rural areas. Materials and methods: The participants were 15 Indonesians who did not work in the nursing and health field. Purposive sampling was used to conduct a descriptive qualitative study. Data was gathered through in-depth interview lasting between 45-60 minutes. The data was collected from November 2022 to January 2023 in Bantul, Yogyakarta Special Province, Indonesia. Data analysis was conducted using Colaizzi's techniques and NVivo 12TM Plus. Results: The data analysis revealed four themes with consisted of two images include: Positive image of nurses: 1) Character traits of nurses; 2) Nurses’ roles and responsibilities; and 3) Expectation for nurses. Then, the negative image of nurses with the theme: 4) Negative perception of nurses. Conclusion: The Indonesian public perceived the brand image of nursing in two ways both positively and negatively. Nursing brand image was perceived by society majority in positive view, such as caring, frontliner for taking care Covid-19 patient, being more professional; however some negative insight persist, included physician assistant and arrogant behavior. It is suggested for nursing profession needs to campaign for a new brand image of nursing that emphasizes the professionalism